2000
DOI: 10.1002/1099-0682(200011)2000:11<2351::aid-ejic2351>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structure of a Palladium Metallacyclic Complex: A Key Intermediate in the Carbonylation of Azobenzene to N ‐Phenyl Urethane

Abstract: The reductive carbonylation of azoxybenzene to N‐phenyl urethane via azobenzene is promoted by the catalytic system based on palladium, bidentate nitrogen‐donor chelating ligands N‐N [N‐N = 1,10‐phenanthroline (phen) and its substituted derivatives] and the acid cocatalyst [(N‐N)H][PF6], the same catalyst as for the reductive carbonylation of nitroaromatic compounds to the corresponding carbamates. The possible key intermediate of the azobenzene → N‐phenyl urethane transformation has been synthesised and fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Note that CO insertion into the PdN bond of C4a can also occur; this would afford the palladacycle generally proposed and observed for Pd–1,10‐phenanthroline nitrobenzene reduction systems 28. 39…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Note that CO insertion into the PdN bond of C4a can also occur; this would afford the palladacycle generally proposed and observed for Pd–1,10‐phenanthroline nitrobenzene reduction systems 28. 39…”
Section: Discussionmentioning
confidence: 81%
“…32, 56 During the proposed catalytic cycle the catalyst remains in the Pd II oxidation state; in the final MPC‐generating step, Pd 0 is regenerated from a palladacyclic intermediate such as that shown in Scheme 28. 39…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few years ago, Mestroni and co-workers showed that the palladium-phenanthroline system is also able to catalyse the carbonylation of azo derivatives and a metallacyclic intermediate was isolated. 99 However, it is our experience that this reaction is much slower than the carbonylation of nitroarenes and is not very effective for the remediation of an impure product.…”
Section: The Palladium-phenanthroline Catalytic System For the Produc...mentioning
confidence: 99%